Study on the mechanical characteristics of a fibre reinforced flexible pipe under radial compression loads - Sun, Zhenwen; Huang, Weiping; Lu, Hailong; Yan, Jun; Yin, Yuanchao; Bu, Yufeng (Frontiers in Materials, 2023)
Fibre reinforced flexible pipes are subjected to radial compression loads caused by the tensioner during pipe laying, which may lead to excessive deformation or even damage of the pipe. In this study, the mechanical characteristics of a glass fibre reinforced unbonded flexible pipe are investigated under radial compression loading. In the theoretical analysis, the hoop reinforcement layer of the pipe is considered equivalent to an orthotropic circular tube. An analytical equation for calculating the radial stiffness of the circular tube per unit length is then derived based on the classical elastic buckling theory. Radial compression tests are carried out with a universal testing machine and displacement loading within the elastic deformation range is applied to two 500mm long samples. A 3D numerical model is established to simulate the compression process of the flexible pipe, through which the distribution characteristics of the displacement, strain and stress of the hoop reinforcement layer are also obtained. The load-displacement curves obtained from the tests and numerical model are linearly fitted to calculate the radial stiffness of the pipe. The radial stiffness obtained by the numerical model is very close to that obtained by the analytical method. However, owing to factors such as material defects and initial ovality, the radial stiffness measured experimentally is lower than the analytical result.